FAKTOR-FAKTOR YANG MEMPENGARUHI ADOPSI INOVASI PERTANIAN SAYUR ORGANIK DI KOTA BATU - Jabal Tarik Ibrahim; Ary Bakhtiar; Dicky Adithya Pratama; Lia Nita Pramudiastuti; Fithri Mufriantie (Jurnal Sosial Ekonomi Pertanian (J-SEP), 2020)
Batu City is an agricultural area that implements an organic farming system. the emergence of organic farming system as part of a sustainable agriculture system which is one of the answers to the degradation of the agricultural environment, the dependence of farmers on the components of the green revolution and the fading of local wisdom in farmers is very important to get serious attention. The purpose of this research is to describe the perceptions and analyze the factors of adoption of innovations in organic vegetable farming in Batu City. The method of taking the population and the sample of this study were determined by the census method. The data analysis method uses descriptive analysis and Partial Least Square. The results of this study indicate that the characteristics of farmers, the nature of technology and the competency of instructors have a positive and significant effect on the adoption of innovations. The factor that has the most influence on the adoption of organic vegetable farming innovations in Batu City is the competency of extension workers. Recommendations that can be given are frequent counseling about organic agriculture and there must also be an understanding of the mindset of the extension participants so that counseling runs optimally.